2013
DOI: 10.2174/1874434601307010133
|View full text |Cite
|
Sign up to set email alerts
|

Factors Involved in Iranian Women Heads of Household’s Health Promotion Activities: A Grounded Theory Study

Abstract: We aimed to explore and describe the factors involved in Iranian women heads of household’s health promotion activities. Grounded theory was used as the method. Sixteen women heads of household were recruited. Data were generated by semi structured interviews. Our findings indicated that remainder of resources (money, time and energy) alongside perceived severity of health risk were two main factors whereas women’s personal and socio-economic characteristics were two contextual factors involved in these women'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…All study participants suggested policy provisions to help working mothers. Previous studies have emphasized government policy changes and recommended flexible work schedules, with specific provisions for breastfeeding mothers who were returning to work (Rafii et al, 2013;Ahmadifaraz et al, 2014). In an Islamic country such as Iran, there is a strong commitment to family, and legislation encourages employers to offer nine months of paid maternity leave to mothers employed by government agencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All study participants suggested policy provisions to help working mothers. Previous studies have emphasized government policy changes and recommended flexible work schedules, with specific provisions for breastfeeding mothers who were returning to work (Rafii et al, 2013;Ahmadifaraz et al, 2014). In an Islamic country such as Iran, there is a strong commitment to family, and legislation encourages employers to offer nine months of paid maternity leave to mothers employed by government agencies.…”
Section: Discussionmentioning
confidence: 99%
“…Iran is a developing country with a population of over 75 million, in which women make up 27% of the workforce (Statistical Center of Iran, ). Employment during pregnancy and while breastfeeding is a relatively new phenomenon in Iran (Ahmadifaraz et al ., ), as Islamic principles encourage women and mothers to focus first on family responsibilities to build a strong foundation and later on their career (Rafii et al, ). Employed mothers fulfill sociocultural expectations of family affairs while managing working‐related challenges (Ahmadi & Taghavi, ).…”
Section: Introductionmentioning
confidence: 99%
“…The number of female-headed households has increased dramatically in the recent half-century, especially in developing countries [6], due to divorce, spouse death, addiction or disability of husband, increased life expectancy among women, migration, or being abandoned by husband [7,8]. According to worldwide statistics, the rates of female-headed households in different countries vary.…”
Section: Introductionmentioning
confidence: 99%
“…Women are among the most prestigious groups of society because they form the foundation of family and society's health [6,21]. Providing them with the care they need is possible when there would be a broad and comprehensive view of their situation and problems [22].…”
Section: Introductionmentioning
confidence: 99%
“…This research is also done by Rafi et al (2013), in which they indicated that the remainder of resources and the perceived severity of health risk were the main factors and women's personal and socio-economic characteristics were the contextual factors involved in the health promotion activities of the participants. However they have focused more on economic condition but they also have resulted in a positive relationship between participation and social health of female headed households.…”
Section: Jssmentioning
confidence: 98%